2021
DOI: 10.1021/acschemneuro.0c00811
|View full text |Cite
|
Sign up to set email alerts
|

Aβ Oligomers Dysregulate Calcium Homeostasis by Mechanosensitive Activation of AMPA and NMDA Receptors

Abstract: Alzheimer’s disease, which is the most common form of dementia, is characterized by the aggregation of the amyloid β peptide (Aβ) and by an impairment of calcium homeostasis caused by excessive activation of glutamatergic receptors (excitotoxicity). Here, we studied the effects on calcium homeostasis caused by the formation of Aβ oligomeric assemblies. We found that Aβ oligomers cause a rapid influx of calcium ions (Ca 2+ ) across the cell membrane by rapidly activating extrasynaptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 72 publications
0
58
0
Order By: Relevance
“…The effects of Aβ on NMDARs have attracted considerable interest as these ligand-gated channels are involved in synaptic plasticity and LTP [ 184 ]. Indeed, Aβ oligomers can induce the overactivation of NMDARs, resulting in a cytosolic Ca 2+ increase [ 77 , 137 , 153 , 185 , 186 ] through several mechanisms: by affecting glutamate availability [ 187 , 188 ] and/or by modifying NMDAR electrophysiological properties [ 189 ], or by changing membrane tension [ 190 ]. Importantly, the overactivation of GluN2B NMDAR subunits induced by Aβ [ 191 ] has been correlated to ER stress, to the depolarization and dysfunction of mitochondria [ 192 , 193 ], to microtubule disassembly and to a reduction in neurite length [ 191 ].…”
Section: Calcium Dyshomeostasis In Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The effects of Aβ on NMDARs have attracted considerable interest as these ligand-gated channels are involved in synaptic plasticity and LTP [ 184 ]. Indeed, Aβ oligomers can induce the overactivation of NMDARs, resulting in a cytosolic Ca 2+ increase [ 77 , 137 , 153 , 185 , 186 ] through several mechanisms: by affecting glutamate availability [ 187 , 188 ] and/or by modifying NMDAR electrophysiological properties [ 189 ], or by changing membrane tension [ 190 ]. Importantly, the overactivation of GluN2B NMDAR subunits induced by Aβ [ 191 ] has been correlated to ER stress, to the depolarization and dysfunction of mitochondria [ 192 , 193 ], to microtubule disassembly and to a reduction in neurite length [ 191 ].…”
Section: Calcium Dyshomeostasis In Alzheimer’s Diseasementioning
confidence: 99%
“…We have recently observed that lysophosphatidylcholine and arachidonic acid, which cause membrane compression and stretch, respectively, can activate NMDAR and AMPAR through a change in membrane tension induced by Aβ oligomers [ 190 ]. In particular, lysophosphatidylcholine is able to neutralize the oligomer-induced activation of the NMDA receptors, whereas arachidonic acid activates the receptors similarly to the oligomers with no additive effects, suggesting that Aβ-induced toxicity can also be caused by the perturbation of the mechanical properties of lipid membranes sensed by NMDA and AMPA receptors [ 190 ]. Memantine, an NMDAR antagonist, was approved in 2002 as a therapeutic drug in moderate to severe AD [ 197 , 198 ].…”
Section: Calcium Dyshomeostasis In Alzheimer’s Diseasementioning
confidence: 99%
“…44,74 Recently, a study demonstrates that ADDLs activate NMDARs and α-amino-3-hydroxy-5-methyl-isoxazolepropionic acid (AMPA) receptors by interacting with the lipid membrane and perturbing the mechanical properties of the membrane, which is sensed by NMDARs and AMPA receptors. 75…”
Section: N-methyl D-aspartate Receptorsmentioning
confidence: 99%
“…Mounting evidence suggested that the Aβ oligomers inhibited the NMDAR‐mediated LTP and promoted LTD. Studies also indicated that the Aβ oligomers‐mediated LTP inhibition involves the activation of the GluN2B subunit of NMDARs 44,74 . Recently, a study demonstrates that ADDLs activate NMDARs and α‐amino‐3‐hydroxy‐5‐methyl‐isoxazolepropionic acid (AMPA) receptors by interacting with the lipid membrane and perturbing the mechanical properties of the membrane, which is sensed by NMDARs and AMPA receptors 75 …”
Section: Mechanism Of Toxicity Mediated By Aβ Oligomersmentioning
confidence: 99%
“…Another mechanism that can cause the misfolding of tau and subsequent formation of its pathogenic version is the extracellular deposition of Aβ [125]. A striking study from Fani and colleagues [126] has shown that extracellular Aβ oligomers are able to principally activate extrasynaptic NMDARs, but also AMPARs to a lower extent. This is carried out by interacting with the lipid membrane that perturbs its mechanical properties, leading to alterations in the mechanosensitivity of receptors (Figure 3) [126].…”
Section: Pathogenic Tau In Synapsesmentioning
confidence: 99%